Hubungan Antara Keterikatan Kerja dengan Intensi Keluar Kerja pada Karyawan Swalayan di Banda Aceh - Risana Rachmatan; Sella Kubatini (Jurnal Online Psikogenesis, 2018)
The existence of employees have an important role in determining the company’s effectiveness and efficiency level, therefore, the company must realize the importance of human resources, in order to a few employees who want to resign (turnover). Before resign, the employees will wolk on some cognitive process that called intention. One of the factors that can be decrease turnover intention is work engagement. This study aimed to determine the relationship between work engagement with employee’s turnover intention at Department Store X in Banda Aceh. This study was conducted of 54 contract employees at Department Store X in Banda.. Data were collected by using a scale adaptation of Utrecht Work Engagement Scale (UWES) and Turnover Intention Scale (TIS). Collected data were analyzed using Pearson Product-Moment Correlation which showing correlation coefficient (r) of -0.695 with p = 0.000 (p 0.05). The result showed that there is a negative relationship between work engagement with turnover intention. It means, if the work engagement of employees is high, turnover intention or otherwise will be lower. The results also showed that the majority of the level of work engagement on contract employees at Department store X Banda Aceh include into the average category (61.11%) and turnover intention are in the low category (31.48%).